Konsep dan Praktik Mengelola Dokumen Dana Kas untuk Pelaporan Bisnis - Mayangsari, Sekar; Arsjah, Regina Jansen; Oktaviani, Ayu Aulia; Yumiarsi; Syahilul Amri (Dirkantara Indonesia, 2025)
This Community Service program aimed to enhance the competencies of vocational school teachers in West Jakarta in accounting, particularly in the management of petty cash. The initiative was motivated by the limited understanding among teachers regarding petty cash recording and reporting, which is a crucial component of the accounting cycle. A total of 30 uncertified vocational school teachers participated in this intensive training, designed to be both comprehensive and interactive. The implementation method consisted of three stages: preparation, execution, and evaluation. Training materials covered basic concepts of petty cash, recording procedures, case examples, and practical exercises guided by expert instructors. Evaluation was carried out using pre-tests and post-tests to measure the participants’ improvement. The results showed a significant increase in participants’ understanding, as indicated by higher average post-test scores compared to pre-test scores. These findings confirm that the training effectively enhanced teachers’ vocational accounting competencies. The program highlights the importance of continuing similar training with broader coverage and sustainability to strengthen vocational education quality in Indonesia.